2020
DOI: 10.20546/ijcmas.2020.903.353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diazotrophic Bacteria on Growth and Biomass Production of Sugarcane invitro

Abstract: 250 to 400 kg ha -1 is only 20-30% and hence at every harvest of the crop, soil suffers a net loss of 50-100 kg N/ha. One avenue to remediate the problem associated with synthetic N fertilizers is the use of microbes capable of biological N 2 fixation (BNF) (de Carvalho et al., 2011). Free-livingN 2 -fixing bacteria belonging to the genera Beijerinckia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Singh et al [103], verifying the potential of nitrogen-fixing rhizobacteria, found that Bacillus species isolated from the root system of sugarcane plants could produce ammonia and showed high nitrogenase activity in vitro. This explains the promotion of N uptake by sugarcane by applying B. licheniformis and B. subtilis [36,81,104]. Under water stress, PGPB promoted a 60.8% increase in N content compared to the control, corroborating Gírio et al [37], who studied sugarcane PSS inoculated with PGPB associated with the application of N in low-fertility soils and found gains in initial growth, dry matter mass, and root length, regardless of fertilizer application, resulting in a positive physiological effect of the bacteria on sugarcane growth.…”
Section: Discussionmentioning
confidence: 93%
“…Singh et al [103], verifying the potential of nitrogen-fixing rhizobacteria, found that Bacillus species isolated from the root system of sugarcane plants could produce ammonia and showed high nitrogenase activity in vitro. This explains the promotion of N uptake by sugarcane by applying B. licheniformis and B. subtilis [36,81,104]. Under water stress, PGPB promoted a 60.8% increase in N content compared to the control, corroborating Gírio et al [37], who studied sugarcane PSS inoculated with PGPB associated with the application of N in low-fertility soils and found gains in initial growth, dry matter mass, and root length, regardless of fertilizer application, resulting in a positive physiological effect of the bacteria on sugarcane growth.…”
Section: Discussionmentioning
confidence: 93%